Analisis Karakteristik Dielektrik Berbagai Minyak Nabati Sebagai Alternatif Isolasi Cair untuk Transformator Tenaga - Gustio Riki Kartiko Anggara; Suprihadi Prasetyono; RB. Moch. Gozali (Jurnal Arus Elektro Indonesia, 2022)
This article discusses the analysis of the dielectric characteristics of various vegetable oils as an alternative to liquid insulation for power transformers. Vegetable oil in this study focused on three kinds of vegetable oil, namely kemiri sunan oil, castor oil, and palm oil. This study reviews the dialectical characteristics of the three oils with respect to temperature changes. This vegetable oil will be compared with transformer oil, namely Shell Diala B, to determine the feasibility of vegetable insulating oil. This article uses literature study and data collection methods, using the basic theory of transformers, namely when alternating electric current flows around an iron core, the iron core will turn into a magnet. The results of this study indicate that these three vegetable oils have the same breakdown voltage characteristics to temperature changes, namely at a temperature voltage of 30°C. Furthermore, these three types of oil are still below the standard SPLN 49-1: 1982 which is 30 kV and still do not have the feasibility of transformer insulation oil. When palm oil is increased to 70°C, the breakdown voltage increases quite drastically, which is 48.58 kV. This has met the standard when compared to Sell diala B oil which when the temperature changes 70°C the breakdown voltage is 47.09 kV. Kata Kunci — Karakteristik Dialektrik, Minyak Nabati, Transformator, Minyak Isolasi, Perubahan Suhu